2011
DOI: 10.1111/j.1749-4486.2011.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

Achieving consensus in follow‐up practice for routine ENT procedures: a Delphi exercise

Abstract: Consensus regarding routine follow-up can be reached by using the Delphi process in ENT practice. This can translate into a real change in clinical practice. Furthermore, this process could be applied for consensus building in other related areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Delphi studies have been used on several occasions in the field of ENT to develop consensus on post-operative follow up, developing an ENT undergraduate curriculum and management of otitis media with effusion in cleft palate patients. [3][4][5] Delphi studies, across the specialties, are usually conducted in several rounds and can last for several months largely because of the delays in waiting for responses, attrition of the expert panel and time for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Delphi studies have been used on several occasions in the field of ENT to develop consensus on post-operative follow up, developing an ENT undergraduate curriculum and management of otitis media with effusion in cleft palate patients. [3][4][5] Delphi studies, across the specialties, are usually conducted in several rounds and can last for several months largely because of the delays in waiting for responses, attrition of the expert panel and time for analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This study found a high degree of consensus on what could be expected from a junior registrar, with consultants and trainees agreeing on the skills needed, 12 so this can hopefully be put into practice. The study used a ‘Delphi’ technique, which has been used previously in ENT training matters 13 and, although it has limitations, deserves wider use.…”
mentioning
confidence: 99%